When the Leader is Born as A Competitor (WLBC) - Agus Maulana; Raju Maulana (UPI YPTK Journal of Business and Economics, 2021)
The presence of humans on earth is a gift of leadership and humans are born with their destiny as leaders for themselves, their families, and the surrounding community. The challenges that are faced every day are important factors in shaping the character of one's self and soul so that it has implications for a leader when taking part in society. Jokowi as a figure of a leader who was forced by circumstances, his family, and society formed himself into a leader with a different character, and it is said that an expert is a Servant Leader. Methodology qualitative and narrative descriptive analysis methods on literature review. Comparisons of expert opinions and theories as well as relating several important events in the lives of characters through audio and video as well as real-life stories. Jokowi's leadership has become an inspiration for many people so that the author is interested in seeing and observing more deeply from the historical side of Jokowi, from the selectivity of a biography and the history of success as a company leader, major, governor and president, this is also what makes the writer's way of thinking finding a new view of leadership theory which is referred to in the term WLBC, along with the many theories of styles and characteristics and types of leadership by previous experts, writers and researchers. There are three finding factors that strongly influence the formation of Jokowi's character which are applied in ten indicators, three factors including family, community, and personal responsibility.